2018
DOI: 10.1093/ndt/gfy175
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inflammation in end-stage renal disease and dialysis

Abstract: Under normal conditions, inflammation is a protective and physiological response to various harmful stimuli. However, in several chronic debilitating disorders, such as chronic kidney disease, inflammation becomes maladaptive, uncontrolled and persistent. Systemic persistent inflammation has, for almost 20 years, been recognized as a major contributor to the uraemic phenotype (such as cardiovascular disease, protein energy wasting, depression, osteoporosis and frailty), and a predictor of cardiovascular and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
260
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 320 publications
(269 citation statements)
references
References 55 publications
2
260
0
7
Order By: Relevance
“…A study that evaluated dogs presenting with AKI showed that the ratio of vWF antigen to collagen binding activity was increased, while collagen‐activated platelet aggregation was decreased in AKI when compared to healthy controls . These data are increasingly interesting in light of the evaluation of vWF in patients with chronic renal disease, another physiological state characterized by systemic inflammation . In a consistent pattern with the Kornblith study on TBI, patients with uremia demonstrated both elevated vWF levels and a decreased ratio of ristocetin cofactor activity to vWF antigen.…”
Section: Effect and Functional Variation Of Vwf In Acute And Chronicmentioning
confidence: 58%
“…A study that evaluated dogs presenting with AKI showed that the ratio of vWF antigen to collagen binding activity was increased, while collagen‐activated platelet aggregation was decreased in AKI when compared to healthy controls . These data are increasingly interesting in light of the evaluation of vWF in patients with chronic renal disease, another physiological state characterized by systemic inflammation . In a consistent pattern with the Kornblith study on TBI, patients with uremia demonstrated both elevated vWF levels and a decreased ratio of ristocetin cofactor activity to vWF antigen.…”
Section: Effect and Functional Variation Of Vwf In Acute And Chronicmentioning
confidence: 58%
“…At progressively increasing concentration, these substances exert toxic effects, which eventually become apparent as symptoms of uremia. The altering effects of the uremic milieu on the immune system has been described as uremic inflammation [10,11], and include mechanisms of both immunoactivation and immunosuppression. Uremic inflammation resembles the premature ageing phenotype in many ways.…”
Section: Uremic Inflammationmentioning
confidence: 99%
“…Therefore, our results suggest that it may be necessary to use a combination of the PhA and hs-CRP levels when testing models that predict sarcopenia, frailty, and/or mortality. Chronic inflammatory conditions, which are common in patients with DMCKD, have been recognized as a major contributor to cardiovascular disease, protein energy wasting, osteoporosis, sarcopenia, and frailty [25][26][27].…”
Section: Discussionmentioning
confidence: 99%